A influência da orientação motivacional durante o treinamento de atletas iniciantes no tênis de campo - Hirota, Vinicius Barroso; Hayashi, Daniel Hideki; Marco, Ademir de; Verardi, Carlos Eduardo Lopes [UNESP] (My University, 2011)
The motivation in the sport has been one of the most studied subjects nowadays, as much that some authors say that the motivation is the base for the success of an athlete, that is, the psychological part must also well be stimulated so that if it reaches the maximum level of concentration during a game it will obtains the expected result. Tennis is one of the sports that more grew in recent years, and together with this fast ascension also increased the number of interested in researching in this area of the Psychology of the Sport. The present study has as objective to begin the adaptation and validation of the interest scale and to analyze the influence of the motivational orientation of the athletes in the sportive performance of the Tennis through the application of scale Teosq – Task and Ego Orientation in Sport Questionnaire (DUDA, 1992), translated, adapted and validated by Hirota and De Marco (2006), where we can identify if the individual is guided for a task or an ego’s goal. This research was carried through in a situated academy of Tennis in the City of Cotia – SP – Brazil, counting on the participation of 20 citizens with age between 09 and 18 years of both the practicing sexes of Tennis. The calculation of the Alpha Coefficient of Cronbach was adopted as statistical method, in order to identify the trust worthy and validity of the instrument beyond the average of each orientation, to be able to verify the athlete’s motivational orientation. For the analysis of the results, the Alpha Coefficient was observed high, compared with previous studies, reaching values of orientation for the ego of 0,90, and 0,70 of orientation for task. They had been registered the following averages, 4,20 (+0,93) and 2,42 (+0,85), respectively of orientation for task and ego. With those results we can point that, the scale applied with the proposal to identify the motivational orientation of the athletes of Tennis, revealed efficiency, and trust worthy in its application, and in accordance with the results, the athletes are guided for task, revealing self-determination, selfconfident, more creative and they judge its success for the quality of the carried through work.

A motivação no esporte tem sido um dos temas mais estudados nos dias de hoje, tanto que alguns autores dizem que a motivação é a base para o sucesso de um atleta, ou seja, a parte psicológica também deve ser bem estimulada para que se atinja o nível máximo de concentração durante uma partida e se consiga obter o resultado esperado. O tênis de campo é um dos esportes que mais cresceram nos últimos anos, e com essa rápida ascensão também aumentou o número de interessados em pesquisar nessa área da psicologia do esporte. O presente estudo teve como objetivo dar início à adaptação e validação da escala de interesse e analisar a influência da orientação motivacional dos atletas no desempenho esportivo no tênis de campo com a aplicação da escala Teosq – Task and Ego Orientation in Sport Questionnaire (DUDA, 1992), traduzido, adaptado e validado por Hirota e De Marco (2006a), onde podemos identificar se o indivíduo é orientado para Meta Tarefa ou orientado para Meta Ego. Esta pesquisa foi realizada numa academia de tênis situada na cidade de Cotia (SP), contando com a participação de 20 sujeitos com idade entre 9 e 18 anos de ambos os sexos, praticantes de tênis. Foi adotado como método estatístico o cálculo do Coeficiente Alfa de Cronbach, a fim de coligar a fidedignidade e a validade do instrumento, além da média de cada orientação, podendo assim verificar a orientação motivacional das atletas. Pela análise dos resultados observou-se o Coeficiente Alfa, valor este elevado comparado com estudos anteriores, atingindo valores de orientação para o ego de 0,90, e 0,70 de orientação para tarefa. Foram registradas as seguintes médias, 4,20 (+0,93) e 2,42 (+0,85), respectivamente, de orientação para tarefa e para ego. Com esses resultados podemos apontar que a escala aplicada com a proposta de identificar a orientação motivacional de atletas de tênis de campo mostrou-se eficiente e fidedigna na sua aplicação; e, de acordo com os resultados, os atletas são orientados para a tarefa, mostrando-se mais autodeterminados, autoconfiantes, mais criativos e julgam seu êxito pela qualidade do trabalho realizado.
The motivacional’s orientation influence during the tennis athletes beginners training
Keywords: Evaluation; Motivation; Tennis; Avaliação; Motivação; Tênis